2013
DOI: 10.1128/ec.00269-12
|View full text |Cite
|
Sign up to set email alerts
|

Dual Functions of α-Ketoglutarate Dehydrogenase E2 in the Krebs Cycle and Mitochondrial DNA Inheritance in Trypanosoma brucei

Abstract: The dihydrolipoyl succinyltransferase (E2) of the multisubunit ␣-ketoglutarate dehydrogenase complex (␣-KD) is an essential Krebs cycle enzyme commonly found in the matrices of mitochondria. African trypanosomes developmentally regulate mitochondrial carbohydrate metabolism and lack a functional Krebs cycle in the bloodstream of mammals. We found that despite the absence of a functional ␣-KD, bloodstream form (BF) trypanosomes express ␣-KDE2, which localized to the mitochondrial matrix and inner membrane. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 57 publications
1
42
0
Order By: Relevance
“…3G); the size and fluorescence intensity of the large kinetoplasts indicated kDNA replication still occurred. Similar increases in kinetoplast size, corresponding to continued kDNA replication were observed in RNAi mutants deficient in mitochondrial TAC components (Zhao et al, 2008;Sykes and Hajduk, 2013). Our observations indicate loss of centriolar TbTBCCD1 causes asymmetric mis-segregation of kDNA.…”
Section: Loss Of Kinetoplast-basal-body Linkagesupporting
confidence: 77%
See 1 more Smart Citation
“…3G); the size and fluorescence intensity of the large kinetoplasts indicated kDNA replication still occurred. Similar increases in kinetoplast size, corresponding to continued kDNA replication were observed in RNAi mutants deficient in mitochondrial TAC components (Zhao et al, 2008;Sykes and Hajduk, 2013). Our observations indicate loss of centriolar TbTBCCD1 causes asymmetric mis-segregation of kDNA.…”
Section: Loss Of Kinetoplast-basal-body Linkagesupporting
confidence: 77%
“…Detailed analyses of TAC-kinetoplast association are currently limited to mitochondrial proteins (Ochsenreiter et al, 2008;Zhao et al, 2008;Sykes and Hajduk, 2013). We therefore looked further, by using TEM, at the kDNA mis-segregation phenotype arising following RNAi against TbTBCCD1 (a nonmitochondrial, TAC-associated protein).…”
Section: Loss Of Kinetoplast-basal-body Linkagementioning
confidence: 99%
“…␣-KD is a vital component of energy metabolism in most aerobic prokaryotes and eukaryotes. ␣-KDE1, ␣-KDE2, and ␣-KDE3 mRNAs are constitutively expressed in both BF and PF T. brucei trypanosomes, yet a functional Krebs cycle and ␣-KD activity are present only in PF trypanosomes (12). We showed that ␣-KDE2 is a bifunctional protein that localized to the mitochondrion of BF T. brucei but was not involved in energy production.…”
mentioning
confidence: 76%
“…To determine whether the A6-ASRE protein was synthesized and imported into the mitochondrion, total cell lysates were prepared from T. brucei transfectants and fractionated by differential centrifugation (Ochsenreiter and Hajduk 2006;Sykes and Hajduk 2013). Total cell (T), cytosolic (C), and mitochondrial (M) protein fractions were prepared either before (uninduced) or 24 h post induction with tetracycline (induced) (Fig.…”
Section: A6-asre Protein Import Into Mitochondriamentioning
confidence: 99%
“…Purified mitochondria were further purified into membrane and matrix fractions as previously described (Sykes and Hajduk 2013). In brief, purified mitochondria were incubated in 0.5% Triton X-100, 20 mM HEPES-NaOH (pH 7.6) with protease inhibitor cocktail (Roche) on ice for 45 min.…”
Section: Cell Fractionation and Sds-pagementioning
confidence: 99%